CELLULOSE ACETATE PRODUCTION BY ACETYLATION OF CELLULOSE DERIVED FROM DATE PALM FRONDS - & et al., Jassem (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
Cellulose acetate (CA) is a biopolymer produced from fronds of date palm (type teperzal) which were taken from the Iraqi groves. The steps used to produce (CA); pretreatment, bleaching, acetylation and hydrolysis. Organosolv pretreatment method was used to remove high lignin content under mild and severe conditions using NaOH as a catalyst at the concentration (0.03) M. The conditions of Organosolv pretreatment were used: temperature (125 °C mild, 160 °C severe), pretreatment time 90 min, and ethanol: water ratio 40:60 wt/wt. The acetylation of cellulose with acetic acid was used to produce cellulose tri-(CTA) and di-(CDA) acetate for two ways: with treated and untreated fronds. The conditions of acetylation reaction were used: temperature (50-55) °C and time (1, 2 & 3) h. The product was characterized by the solubility test, titration method and Fourier transform infrared spectroscopy (FTIR). The results showed that the high percentage of lignin removed was (93%), the best degree of substitution (DS) for (CTA) and (CDA) were 3.01 and 2.60. As well as the excellent solubility percentages for (CTA) with chloroform and mixture of chloroform/methanol were 90% and 84%, respectively. While the solubility percentage for (CDA) with acetone was 95%, these result occurred at pretreatment temperature 160°C, pretreatment time 90 min and reaction time 3 h.